Comparison of concept PR 100 and spray-dried animal Plasma on nursery pig performance - E J Wiedmann; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
One hundred eighty weanling pigs (initially 12.1 lb and 18 ± 2 d of age) were used in a 28-d growth assay to determine if Concept PR 100 (CNPR), a plant-based protein ingredient with added synthetic amino acids and nucleic acids, can replace spray-dried animal plasma (SDAP) in nursery pig diets. The five experimental treatments were: 1) control (no specialty protein source); 2) 2.5% SDAP; 3) 5.0% SDAP; 4) 2.5% CNPR; and 5) 5.0% CNPR. Treatment diets were fed from d 0 to 14 after weaning, with a common diet fed to all pigs from d 14 to 28 after weaning. From d 0 to 14, pigs fed increasing amounts of SDAP had improved (linear and quadratic, P<0.01) ADG and ADFI, which was primarily due to a large improvement from 0 to 2.5% SDAP, with a smaller increase when 5.0% was fed. In addition, pigs fed diets containing increasing amounts of CNPR had increased(linear and quadratic, P<0.003) ADG and ADFI, with the maximum response observed in pigs fed 2.5% CNPR. Furthermore, pigs fed increasing amounts of SDAP or CNPR had improved F/G (linear, P<0.001 and quadratic, P<0.07, respectively), compared with F/G of control pigs. When comparing the means of pigs fed diets containing SDAP versus those fed CNPR, pigs fed SDAP had greater (P<0.002) ADG, ADFI, and pig weight at d 14, compared with pigs fed CNPR. Overall, (d 0 to 28), pigs fed increasing amounts of SDAP and CNPR had greater ADG, ADFI, and final weight (linear, P<0.01) than did pigs fed the control diet. The greatest improvement for pigs fed both protein sources was observed at 2.5% inclusion in the diet, with a smaller increase up to a 5.0% inclusion. Although either protein source improved growth performance, compared with the control diet, pigs fed SDAP tended to have greater overall ADG (P<0.12) and final body weight (P<0.11) than pigs fed CNPR.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Swine; Nursery pig; Specialty protein sources; Spray-dried animal plasma; Growth